2011
DOI: 10.20873/jbb.uft.cemaf.v2n1.sobrinho
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of sugar cane juice (Sacharum officinarum) cultivar RB 7515 by wild yeasts resistant to UVC

Abstract: Commercial alcoholic fermentations coexist with microbial contamination come together withsugar cane or industrial water. The contaminants are bacteria or wild yeast that also results reduction in yield. The contaminants control use acid treatment and antibiotics. Disinfection by ultraviolet radiation is efficient in transparent liquid and has as advantage leaving noresidues. Reports on the UV effect over microorganisms in turbid and colored liquids are scarce. The research evaluated the use of commercial UVC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The Brix of raw sugarcane juice was 18.2±2.2. Similar findings were reported by (30) in which the brix was found to range between 14 to 22. Iced sugarcane juice had an average brix of 9.7, which is very low compared to the recommended.…”
Section: Physical-chemical Properties Of Sugarcane Juicesupporting
confidence: 90%
“…The Brix of raw sugarcane juice was 18.2±2.2. Similar findings were reported by (30) in which the brix was found to range between 14 to 22. Iced sugarcane juice had an average brix of 9.7, which is very low compared to the recommended.…”
Section: Physical-chemical Properties Of Sugarcane Juicesupporting
confidence: 90%
“…It contains 126 g/L of total sugars, 98 g/L of non‐reducing sugars, 28 g/L of reducing sugars (Sobrinho et al . ) and 2.20 mg/100 mL of iron (Rawat and Pokhriyal ). Krishnakumar and Devadas () reported that TSS decreased (19–17.1 Brix) with increase in storage period (10–60 days) and the decrease was less (18.7 Brix) in sugarcane juice stored in glass bottles.…”
Section: Resultsmentioning
confidence: 99%
“…The ethanol concentration from 4 to 5% (v/v) observed for the eight fermentative relevant strains, PE‐2 and CAT‐1, is similar to that obtained by wild yeast strains in sugar cane syrup with the same substrate concentration (Sobrinho et al . ).…”
Section: Discussionmentioning
confidence: 97%